Somatic embryogenesis in holm oak male catkins - Blasco, M.; Barra, A.; Brisa, C.; Corredoira, E.; Segura, J.; Toribio, M.; Arrillaga, I. (Plant Growth Regulation, 2013)
Somatic embryogenesis (SE) of tree species is the most promising method for the implementation of multivarietal forestry and for biotechnological approaches. To date, however, the application of this technology to mature trees is restricted to a few species. This is the first report on the induction of SE from male catkins of 100-year-old holm oaks (Quercus ilex L.). Embryogenic competence was mainly dependent on genotype and restricted to the most advanced catkin developmental stage with distinguishable closed flowers along the axis. Fol- lowing a three-stage treatment procedure, embryogenic response (frequencies up 3.3 %) was obtained in three [Remedio, Villar del Arzobispo (VA) and Hunde (HU)] out of the five genotypes evaluated. In the culture conditions tested, the preferred protocol to induce SE in holm oak catkins should include: induction on MS medium with 6-benzyladenine and naphthaleneacetic acid, subculture onto medium with a reduced concentration of both plant growth regulators and a final transference to medium without growth regulators. Under these conditions cotyledonary-stage cotyledonary-stage somatic embryos developed from brown calli with or without nodular structures. Secondary SE, favored by the addition of sorbitol to the manifestation medium, allowed the establishment of 14 embryogenic lines belonging to VA and HU genotypes. Histological observations of the proliferating cultures revealed the presence of globular, torpedo and cotyledonary somatic embryos. Somatic embryos were diploid as verified by flow cytometry analysis, suggesting that they originated from the perianthic tissue of the male flower
Keywords: adult trees; developmental stage; flow cytometry; forest biotechnology; histology; micropropagation; Quercus ilex; secondary embryogenesis

First data from a field trial of Quercus suber plants regenerated from mature selected trees and from their half-sib progenies by somatic embryogenesis - Celestino, C.; Hernández, I.; Lopez-Vela, D.; Carneros, E.; Alegre, J.; Toribio, M.; Fernandez-Guijarro, B.; Cardo, L. (Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants, 2007)
Somatic embryogenesis is considered as the most suitable current regeneration technique for the conservation and genetic improvement of tree species. The ability to induce somatic embryogenesis in leaves from mature trees gives the possibility to compare the performance of the parent trees and their progenies at the same age and place of test. Somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies. They were planted in the field conjointly with zygotic seedlings of these families, to test the comparisons somatic vs. zygotic origin and somatic from mature trees vs. somatic from juvenile seedlings. The effect of genotype and kind of progeny will be studied in a complete factorial design; therefore the field trial comprised 15 treatments arranged in five completely randomised blocks. Each experimental unit included three plants that were distributed following a row and column pattern. Fist survival and height data after six and twelve months of establishment are provided. All plants from seeds survived while almost the half of somatic seedlings died after the winter and they were replaced. Almost 70% of these plants survived after the following summer. There were no differences between somatic seedlings of mature or juvenile origin. Zygotic seedlings doubled the height of the somatic ones after one year in the field, and within these plants those of mature origin grew slightly more than those of juvenile source. Differences due to genotype and family effects were noticeable. No apparent morphological alterations were detected among the three kinds of tested progenies.
The following values have no corresponding Zotero field: periodical: Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants issue: 748 pub-location: PO BOX 500, 3001 LEUVEN 1, BELGIUM
Keywords: Cork oak; field establishment; rejuvenation; Somatic embryogenesis; woody plant micro-propagation

Genetic transformation of selected mature cork oak (Quercus suber L.) trees. - Alvarez, R.; Alonso, P.; Cortizo, M.; Celestino, C.; Hernández, I.; Toribio, M.; Ordás, R. J. (Plant cell reports, 2004)
A transformation system for selected mature cork oak (Quercus suber L.) trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses were inoculated with A. tumefaciens strains EHA105, LBA4404 or AGL1 harbouring the plasmid pBINUbiGUSint [carrying the neomycin phosphotransferase II (nptII) and beta-glucuronidase (uidA) genes]. The highest transformation efficiency (4%) was obtained when freshly isolated explants were inoculated with A. tumefaciens strain AGL1. Evidence of stable transgene integration was obtained by PCR for the nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos were germinated and successfully transferred to soil.
The following values have no corresponding Zotero field: accession-num: 15185122
Keywords: Agrobacterium; Cork oak; Fagaceae; Somatic embryogenesis; Tree genetic transformation

EARLY CHECKING OF GENETIC STABILITY OF CORK OAK SOMATIC EMBRYOS BY AFLP ANALYSIS. - Hornero, J.; Martinez, I.; Celestino, C.; Gallego, F. J.; Torres, V.; Toribio, M. (International Journal of Plant Sciences, 2001)
Early checking of the genetic stability, of tissue culture-derived plants is necessary to obtain all the potential benefits of clonal forestry. Previous work in Quercus suber L. using random amplified polymorphic DNA (RAPD) markers showed no genetic variation among somatic embryos within embryogenic lines of zygotic origin. Genetic fingerprinting based on amplified fragment length polymorphisms (AFLP) allows the direct analysis of variation at the entire DNA level by generating more reproducible markers than RAPDs. To confirm the absence of genetic variation within six embryogenic lines of zygotic origin, six primer pairs were selected out of 48 combinations of primers for revealing up to 512 AFLP markers, 301 of them (58.8%) being polymorphic. The mean number of markers per genotype was 375. Again differences were recorded among embryogenic lines, even between those that arose from half-sib zygotic embryos, but no variation was observed among somatic embryos within embryogenic lines. To check variation in embryogenic lines raised from non-embryonic tissues, somatic embryogenesis was induced in expanding leaves collected from sprouts originating in three mature cork oak. DNA was extracted from leaves and from somatic embryos derived from each tree, and three primer pairs showed 165, 110, and 108 markers per genotype/tree, respectively. In one tree, AFLP patterns generated from leaves and somatic embryos were identical, but variation was detected in samples from the other two trees. Although the level of genetic variation detected in these lines (5.6% and 7.3% of polymorphism, respectively) is lower than that recorded for half sibs of cork oak (25%–31%), its influence on phenotypic variation needs further assessment. [ABSTRACT FROM AUTHOR]
Keywords: AFLP; Cork oak; DNA markers; in vitro culture; Quercus suber; somaclonal variation; Somatic embryogenesis

OBTENCION DE PLANTAS A PARTIR DE EMBRIONES SOMATICOS DE QUERCUS SUBER L - Fernández Guijarro, B.; Celestino, C.; Toribio, M. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This paper gives a procedure to regenerate plants of cork oak through somatic embryogenesis. The somatic embryos were obtained in leaves from young seedlings and cotyledonary fragments from mature acorns of cork oak. The explants were cultured in three stage process in wich BA and NAA concentration were decreasing. Different methods were used to germinate the embryos. Dessication and culture in low salt concentration medium were chosen to give the best results
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: adventive embryogenesis; Cork oak; culture media; plant regeneration; secondary embryogenesis